Comparison of Doses from Disposals of Technologically Enhanced Naturally Occurring Radioactive Materials in Kentucky and Oregon. Issue 6 (17th June 2023) - Caffrey, Emily A.; Rood, Arthur S.; Grogan, Helen A.; Mangini, Colby; Till, John E.
Abstract: Oil and natural gas fracking waste contains technologically enhanced naturally occurring radioactive material (TENORM) and has increasingly been disposed of in unpermitted landfills, causing concern among regulators and the public about potential exposures. There are numerous issues with TENORM waste, including the lack of Federal regulations on its disposal and the lack of permitted landfills capable of accepting these waste streams. This paper examines two situations in which TENORM was placed in unpermitted landfills, one in Kentucky and one in Oregon. The same modeling and dose calculation methods were used in both cases, allowing for a comparison between the two sites. Site-specific differences, source terms, and doses from the disposals and potential remediation options are discussed and compared. Predicted groundwater concentrations are shown and compared against the relevant regulations for each site. Despite the differences in site and TENORM waste characteristics, it was more protective of the community and the environment to leave the waste in place at both sites. Radiation doses to landfill workers on site and to members of the public were low, both during the original disposal and for the remediation alternatives evaluated. Removal of the TENORM material in either case presents significant non-radiological risks that outweigh any benefit from the long-term dose reduction.